A Scientometric Study on Relative Citation Impact of Turkey - Al, Umut (Information World, 2009)
Turkey’s contribution to citation indexes has been increasing every year. This increase has become particularly visible with the inclusion of some of the Turkey addressed journals in the citation indexes. The expansion decision taken by the commercial company that owns citation indexes also plays a significant role in this increase. This study evaluates the relative citation impact of Turkey and includes various comparisons based on country and field of study data. The data used in this study is obtained from Essential Science Indicators. The aim of the study is to examine Turkey’s high and low relative citation impact areas and determine whether there is a change in relative citation impact in time. Our study also tries to expose Turkey’s position in terms of relative citation impact when compared with different countries. The findings indicate that engineering is the highest relative citation impact area in Turkey and plant and animal sciences is the lowest, and no significant changes are observed between the two in time. The United States of America preserves its indisputable leading position in all areas in the scientific world. Turkey, on the other hand, is yet to reach to a level, where it can compete with such countries as England, Germany, Canada and France.